Lithium ion battery precursor, positive electrode material and preparation method and application thereof

By doping the precursor of the lithium-ion battery cathode material with amphoteric metal elements to form an intercalation doping structure, the problem of poor stability of the cathode material at high temperatures is solved, and the cycle life and safety performance of the battery are improved.

CN119330428APending Publication Date: 2025-01-21BATTERO TECH CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411467238.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials have poor stability at high temperatures, which limits the application and cycle life of lithium-ion batteries.

Method used

By doping amphoteric metal elements into the nickel-cobalt-manganese hydroxide precursor, an intercalation-doped lithium-ion battery precursor is formed, and the cathode material is prepared using a co-precipitation method to improve the uniformity and structural stability of the doped elements.

Benefits of technology

The high-temperature cycle life and safety performance of lithium-ion batteries are significantly improved, the capacity retention rate is increased by about 5-10%, and the thermal stability is also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330428A_ABST
    Figure CN119330428A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery precursor, a positive electrode material and a preparation method and application thereof, and relates to the technical field of lithium ion batteries. Metal powder can be added in the process of preparing the precursor, the metal powder reacts with the precursor under the alkaline condition to generate metal oxide, the oxide generated through the reaction is complexed on the outer layer of the continuously-growing precursor to form intercalation doping, and metal ions are evenly distributed on the surface layer between layers of the NCM after sintering. The metal oxide is introduced into the precursor, the metal oxide can form intercalation doping, the doping uniformity is high, the structural stability of the material is improved, the safety of the lithium ion battery is improved, and the high-temperature cycle life of the lithium ion battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery precursor, a positive electrode material, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) are the mainstream energy storage devices for electric vehicles or hybrid vehicles. The positive electrode material is the key factor that determines the capacity of lithium-ion batteries. Current positive electrode materials generally have the problem of poor high-temperature stability, which greatly limits the application of LIBs.

[0003] Modifying the bulk structure and surface chemical properties of the positive electrode material by means of doping and coating is beneficial to improving its high temperature performance. Among them, bulk doping and surface coating are common methods to strengthen the internal structure and surface of the positive electrode material. Bulk doping can effectively inhibit the reversible phase change and volume expansion of the material during the charging process, and at the same time can buffer the changes in the layered structure during lithium insertion and extraction, reduce the reaction between the material and the various components of the battery in the charged state, reduce the generation of microcracks inside the secondary particles and the erosion of the electrolyte on the secondary particles, thereby improving the cycle life and safety performance of the material; surface coating can establish a stable protective layer to avoid direct contact between the electrode and the electrolyte.

[0004] The doping process of lithium-ion battery positive electrode materials mostly adopts co-precipitation method and solid phase grinding method. The number, doping position and uniformity of doped ions are difficult to control, and the improvement effect is also limited. Therefore, it is necessary to propose a simple preparation method to improve the ion doping level, reduce lithium-nickel mixing, and improve the safety and high-temperature cycle life of lithium-ion batteries.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a lithium ion battery precursor, a positive electrode material and a preparation method and application thereof, aiming to improve the structural stability of the material and increase the high temperature cycle life of the lithium ion battery.

[0007] The present invention is achieved in that:

[0008] In a first aspect, the present invention provides a lithium ion battery precursor, comprising a nickel-cobalt-manganese hydroxide precursor, wherein a metal element is doped in the nickel-cobalt-manganese hydroxide precursor;

[0009] The metal elements are amphoteric metal elements.

[0010] In an optional embodiment, the metal element is present in the lithium-ion battery precursor in the form of intercalation doping;

[0011] Preferably, the metal element in the metal oxide is selected from at least one of Al, Zn, Ga, Ge, In, Sn, Sb, Tl, Pb and Bi;

[0012] Preferably, the metal element in the metal oxide is Zn.

[0013] In an optional embodiment, the chemical formula of the lithium ion battery precursor is Ni x Co y Mn (1-x-y-z) M Z O(OH) 2 , M represents an amphoteric metal element, 0.8≥x≥0.5, 0.05≥y≥0, 0.05≥z≥0.

[0014] In a second aspect, the present invention provides a method for preparing a lithium-ion battery precursor according to any one of the aforementioned embodiments, comprising: using nickel salt, cobalt salt, and manganese salt as raw materials to prepare a lithium-ion battery precursor by a coprecipitation method;

[0015] During the coprecipitation process, metal powder containing amphoteric metal elements is added.

[0016] In an optional embodiment, it includes:

[0017] providing a mixed salt solution containing nickel salt, cobalt salt and manganese salt;

[0018] providing a precipitant solution and a complexing agent solution;

[0019] The mixed salt solution, the precipitant solution and the complexing agent solution are introduced into a reactor for coprecipitation reaction. During the reaction, the metal powder is added together with the mixed salt solution until the reaction is completed. The reaction is stopped when the crystal particle size reaches 2 μm-6 μm.

[0020] In an optional embodiment, the molar ratio of nickel, cobalt, manganese and amphoteric metal elements added during the reaction is x:y:(1-xyz):z; 0.8≥x≥0.5, 0.05≥y≥0, 0.05≥z≥0;

[0021] Preferably, the pH value of the coprecipitation reaction is controlled to be 9-13, and the concentration of the complexing agent in the reactor is 0.4-10;

[0022] Preferably, the total concentration of metal elements in the mixed salt solution is 0.1mol / L-2mol / L, the concentration of the precipitant solution is 0.4mol / L-10mol / L, and the concentration of the complexing agent solution is 0.4mol / L-10mol / L;

[0023] More preferably, the precipitant solution is a sodium hydroxide solution and the complexing agent solution is an ammonia solution;

[0024] More preferably, the mixed salt solution addition rate is controlled to be 40 mL / h-60 mL / h, so that the power obtained per unit volume of solution is 0.3-6 kW / m 3 .

[0025] In a third aspect, the present invention provides a lithium-ion battery positive electrode material, whose chemical formula is LiNi x Co y Mn (1-x-y-z) M z O 2 @N a O;

[0026] Wherein, M is an amphoteric metal element;

[0027] N represents a surface coating element, and N is selected from at least one of B, Zr, Ti, La, V, Mo, Cr, Zn, W and Al;

[0028] 0.8 ≥ x ≥ 0.5, 0.05 ≥ y ≥ 0, 0.05 ≥ z ≥ 0;

[0029] Preferably, M is selected from the group consisting of Al, Zn, Ga, Ge, In, Sn, Sb, Tl, Pb and Bi, which are present in the positive electrode material of the lithium ion battery in the form of intercalation doping; M is selected from at least one of Al, Zn, Ga, Ge, In, Sn, Sb, Tl, Pb and Bi;

[0030] Preferably, the content of M in the positive electrode material of the lithium ion battery is 100 ppm-10000 ppm.

[0031] In a fourth aspect, the present invention provides a method for preparing a positive electrode material for a lithium ion battery, wherein a lithium ion battery precursor is prepared by using the preparation method of any one of the aforementioned embodiments, and the lithium ion battery precursor is mixed with a lithium source and sintered once;

[0032] Preferably, the molar ratio of lithium element in the lithium source to the total amount of nickel, cobalt, manganese and amphoteric metal elements in the lithium ion battery precursor is controlled to be (0.9-1.2):1:(0.1-1); preferably, sintering is carried out once in an oxygen-containing atmosphere, the sintering temperature is controlled to be 600°C-1100°C, and the sintering time is 3h-20h.

[0033] In an optional embodiment, after the primary sintering, the obtained material is mixed with a compound containing an element N for secondary sintering; N is selected from at least one of B, Zr, Ti, La, V, Mo, Cr, Zn, W and Al;

[0034] Preferably, the secondary sintering is carried out in an oxygen-containing atmosphere, the secondary sintering temperature is controlled to be 300° C.-800° C., and the sintering time is 3 h-20 h;

[0035] Preferably, the material obtained after the primary sintering is first crushed, then washed and dried, and then mixed with a compound containing the N element for secondary sintering.

[0036] In a fifth aspect, the present invention provides a secondary battery, comprising the lithium-ion battery positive electrode material of the aforementioned embodiment or the lithium-ion battery positive electrode material prepared by the preparation method of any one of the aforementioned embodiments.

[0037] The present invention has the following beneficial effects: by introducing metal oxide into the precursor, the metal oxide can form intercalation doping, and the doping uniformity is high, which is beneficial to improving the structural stability of the material and improving the safety and high-temperature cycle life of the lithium-ion battery.

[0038] It should be added that metal powder can be added in the process of preparing the precursor. The metal powder reacts with it under alkaline conditions to form metal oxides. The oxides generated by the reaction are complexed in the outer layer of the growing precursor to form intercalation doping. After sintering, the metal ions are evenly distributed on the surface between the layers of NCM. The metal ions enter the lithium layer. Since the metal ions do not react in the system, the lithium-nickel mixing can be inhibited. The metal substitution of Mn ions will increase the average oxidation state of Mn and reduce the unstable Mn in the particle phase and on the surface. 3+ The modified bulk structure and surface can inhibit the dissolution of Mn. In addition, doping ions also increases the volume of the material lattice, improves the transmission efficiency of lithium ions, and reduces the c / a value of the lattice. During the lithium ion deintercalation process, the lattice is more difficult to transform into the monoclinic phase and hexagonal phase, improving the internal structure and surface stability of the crystal. Even at high temperatures, the capacity will not be sacrificed, and the modified battery has significant improvements in safety and high-temperature cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0040] Figure 1 The graphs are the test results of the cycle performance of the positive electrode materials prepared in the examples and comparative examples;

[0041] Figure 2 The figure is a result diagram of the positive electrode materials prepared in the examples and comparative examples using a differential scanning calorimeter (DSC). DETAILED DESCRIPTION

[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0043] Most of the existing ternary material doping processes use co-precipitation and solid phase grinding doping methods, which have the problem that the number of doping ions, doping positions and uniformity are difficult to control. To address this problem, the inventors optimized the preparation process of the positive electrode material, especially the method of introducing doping elements, to improve the uniformity of the distribution of doping elements.

[0044] The embodiment of the present invention provides a method for preparing a positive electrode material for a lithium-ion battery. First, the preparation process of the precursor is optimized to form an intercalation-doped precursor, and finally a positive electrode material with an intercalation ternary layered structure is prepared. Specifically, the preparation process includes the following steps:

[0045] S1. Preparation of lithium-ion battery precursors

[0046] An embodiment of the present invention provides a method for preparing a lithium-ion battery precursor, comprising: using nickel salt, cobalt salt, and manganese salt as raw materials, and adopting a coprecipitation method to prepare a lithium-ion battery precursor; during the coprecipitation process, adding metal powder containing amphoteric metal elements, and the metal powder reacts with the amphoteric metal elements under alkaline conditions to generate metal oxides, thereby forming intercalation doping.

[0047] “Intercalation doping” refers to the uniform doping of doping elements in layered ternary materials.

[0048] The process of preparing lithium-ion battery precursors includes the following steps:

[0049] (1) Preparation

[0050] A mixed salt solution, a precipitant solution, a complexing agent solution and metal powder (metal powder containing amphoteric metal elements) are prepared separately.

[0051] A mixed salt solution containing nickel salt, cobalt salt and manganese salt is prepared by mixing nickel salt, cobalt salt and manganese salt in water. The nickel salt, cobalt salt and manganese salt can be selected from at least one of sulfate, chloride, nitrate and acetate, and the types of the nickel salt, cobalt salt and manganese salt can be the same or different, and can be independently selected from any one or more of the above. Preferably, the nickel salt, cobalt salt and manganese salt can all be sulfates, the raw materials are easily available, and the precipitation process is easy to control.

[0052] In some embodiments, the total concentration of metal elements in the mixed salt solution is 0.1mol / L-2mol / L (such as 0.1mol / L, 0.5mol / L, 1.0mol / L, 1.5mol / L, 2.0mol / L, etc.), and the ratio of nickel, cobalt and manganese is not limited, and the ingredients are prepared according to the molar ratio of nickel, cobalt and manganese elements in the precursor target product. The molar ratio of nickel, cobalt and manganese and amphoteric metal elements added during the reaction is x:y:(1-xyz):z; 0.8≥x≥0.5, 0.05≥y≥0, 0.05≥z≥0.

[0053] In some embodiments, the type of precipitation agent is not limited, and can be sodium hydroxide, but is not limited thereto. The precipitation agent solution can be an aqueous solution, and the concentration of the precipitation agent solution is 0.4mol / L-10mol / L (such as 0.4mol / L, 1.0mol / L, 3.0mol / L, 5.0mol / L, 8.0mol / L, 10mol / L, etc.). The type of complexing agent is not limited, and can be ammonia water, but is not limited thereto. The concentration of the complexing agent solution is 0.4mol / L-10mol / L (such as 0.4mol / L, 1.0mol / L, 3.0mol / L, 5.0mol / L, 8.0mol / L, 10mol / L, etc.). By regulating the concentration of the precipitation agent solution and the complexing agent solution, the pH value and the complexing agent concentration in the precipitation process are more easily controlled.

[0054] In some embodiments, the metal powder is a metal powder containing an amphoteric metal element, selected from at least one of Al, Zn, Ga, Ge, In, Sn, Sb, Tl, Pb and Bi, and may be any one or more of the above. Preferably, the metal powder is zinc, which can react with NaOH under alkaline conditions to form an oxide to obtain nickel-cobalt-manganese hydroxide doped with metal oxides.

[0055] (2) Coprecipitation reaction

[0056] The mixed salt solution, precipitant solution and complexing agent solution are introduced into the reactor for coprecipitation reaction. During the reaction, metal powder is added together with the mixed salt solution until the reaction is completed. The reaction is stopped when the crystal particle size reaches 2μm-6μm. During the reaction, the metal powder reacts with NaOH under alkaline conditions to generate oxides, and the synthesis of nickel-cobalt-manganese hydroxide doped with metal oxides is carried out to form an intercalated ternary layered structure material. The oxides (such as zinc oxide) generated during the reaction are uniformly complexed in the outer layer of the growing precursor.

[0057] In a preferred embodiment, metal powder is continuously added during the reaction process to form uniform intercalation doping. The pH value of the coprecipitation reaction is controlled to be 9-13, and the concentration of the complexing agent in the reactor is 0.4-10. The deposition is uniformly performed by adjusting the reaction pH value and the concentration of the complexing agent to improve the uniformity of the element distribution in the precursor. The reaction process can be carried out under the protection of an inert gas (such as nitrogen), and the reaction process is combined with low-speed stirring to make the crystals grow uniformly. After the precipitation is completed, filtering, washing, and drying are performed to obtain a metal oxide-doped precursor.

[0058] Furthermore, the molar ratio of nickel, cobalt, manganese and amphoteric metal elements added during the reaction is x:y:(1-xyz):z; 0.8≥x≥0.5, 0.05≥y≥0, 0.05≥z≥0, so that the ratio of each element in the obtained precursor meets the preset requirements.

[0059] In a preferred embodiment, the mixed salt solution addition rate is controlled to be 40 mL / h-60 mL / h (such as 40 mL / h, 50 mL / h, 60 mL / h, etc.), so that the power obtained per unit volume of solution is 0.3-6 kW / m 3 , such as 0.3kW / m 3 , 0.5kW / m 3 , 1.0kW / m 3 , 2.0kW / m 3 、3.0kW / m 3 , 4.0kW / m 3 、5.0kW / m 3 、6.0kW / m 3 wait.

[0060] Aluminum salt can also be added to the mixed salt solution used in the co-precipitation process. The introduction of a small amount of aluminum is also beneficial to improving the electrochemical properties of the product.

[0061] A lithium-ion battery precursor provided in an embodiment of the present invention includes a nickel-cobalt-manganese hydroxide precursor, in which a metal element is doped; the metal element is an amphoteric metal element. By introducing the amphoteric metal element into the precursor, the amphoteric metal element can form intercalation doping, and the uniformity of the doping is high, which is beneficial to improving the structural stability of the material and improving the safety and high-temperature cycle life of the lithium-ion battery. The process of preparing the lithium-ion battery precursor can refer to the preparation method provided in the embodiment of the present invention.

[0062] Furthermore, the amphoteric metal element is present in the lithium-ion battery precursor in the form of intercalation doping, and the metal element in the metal oxide is selected from at least one of Al, Zn, Ga, Ge, In, Sn, Sb, Tl, Pb and Bi, and the metal element can be any one or more of the above. Preferably, the metal element in the metal oxide is Zn, and the use of zinc for intercalation doping can further improve the electrochemical performance of the product.

[0063] In some embodiments, the chemical formula of the lithium-ion battery precursor is Ni x Co y Mn (1-x-y-z) M Z O(OH) 2 , M represents an amphoteric metal element, 0.8≥x≥0.5, 0.05≥y≥0, 0.05≥z≥0.

[0064] It should be added that the prior art forms a metal-doped precursor by adding metal salts or metal oxides to the precursor. However, due to the differences in the Ksp of metal salts, the metal salts precipitate differently. Direct addition in the form of metal oxides and addition of metal oxides during sintering can lead to uneven doped metal ions, resulting in rapid performance deterioration. The present invention uses metal powders to add doping elements to form metal oxides that exist in the lithium-ion battery precursor in the form of intercalation doping, significantly improving the uniformity of doping element distribution. Specifically, Zn first reacts with NaOH solution in the solution to generate Zn(OH) 2 , dissolves in strong alkali to form zincate, which can dissolve in ammonium salt or ammonia water to form zinc ammine complex ions:

[0065] Zn(OH) 2 +2NH 3 ·H 2 O+2NH 4 + =[Zn(NH 3 ) 4 ] 2+ +2H 2 O;

[0066] The complex ions will further undergo hydrolysis:

[0067] [Zn(NH 3 ) 4 ] 2+ +2H 2 O=ZnO+2NH 4 + +2NH 3 ·H 2 O.

[0068] S2, primary sintering

[0069] The lithium-ion battery precursor prepared by S2 is mixed with a lithium source and sintered once. After program-controlled temperature sintering, the metal ions are evenly distributed on the surface between the layers of NCM.

[0070] In some embodiments, the molar ratio of lithium in the lithium source to the total amount of nickel, cobalt, manganese and amphoteric metal elements in the lithium-ion battery precursor is controlled to be (0.9-1.2):1:(0.1-1), such as 0.9:1:0.1, 1.0:1:0.3, 1.1:1:0.7, 1.2:1:1.0, etc., and it is preferred that lithium is in slight excess.

[0071] Furthermore, a sintering is carried out in an oxygen-containing atmosphere, the sintering temperature is controlled to be 600°C-1100°C (such as 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, etc.), and the sintering time is 3h-20h (such as 3h, 5h, 10h, 15h, 20h, etc.). By optimizing the sintering temperature and time, the reaction is fully carried out to obtain a uniform oxide.

[0072] After sintering is completed, the material is naturally cooled in the furnace and then crushed and pulverized, then washed and dried before entering the next stage for secondary sintering.

[0073] S3, secondary sintering

[0074] After the primary sintering, the obtained material is mixed with a compound containing the N element and subjected to secondary sintering, so that the N element plays the role of surface coating.

[0075] In some embodiments, N is selected from at least one of B, Zr, Ti, La, V, Mo, Cr, Zn, W and Al. N can be any one or more of the above. By introducing surface coating elements, the electrochemical properties of the positive electrode material can be further improved.

[0076] Further, secondary sintering is performed in an oxygen-containing atmosphere, the secondary sintering temperature is controlled to be 300°C-800°C (such as 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, etc.), and the sintering time is 3h-20h (such as 3h, 5h, 10h, 15h, 20h, etc.), and the N element is uniformly coated on the surface of the material by adjusting the temperature and time of the secondary sintering. The sintering atmosphere is not limited, and can be an oxygen atmosphere, but is not limited thereto.

[0077] The present invention also provides a lithium-ion battery positive electrode material, the chemical formula of which is LiNi x Co y Mn (1-x-y-z) M z O 2 @N aO; wherein N represents a coating element, and M is an amphoteric metal element, N represents a surface coating element, and N is selected from at least one of B, Zr, Ti, La, V, Mo, Cr, Zn, W and Al; 0.8≥x≥0.5, 0.05≥y≥0, 0.05≥z≥0. The lithium ion battery positive electrode material can be prepared by the preparation method provided by the embodiment of the present invention, and the doped positive electrode material prepared by the embodiment of the present invention has a more excellent layered structure.

[0078] In some embodiments, M is selected from the positive electrode material of the lithium ion battery in the form of intercalation doping. M is selected from at least one of Al, Zn, Ga, Ge, In, Sn, Sb, Tl, Pb and Bi, and M can be any one or more of the above elements. The content of M in the positive electrode material of the lithium ion battery is 100ppm-10000ppm, such as 100ppm, 500ppm, 1000ppm, 3000ppm, 5000ppm, 8000ppm, 10000ppm, etc.

[0079] In some embodiments, the N content in the positive electrode material of the lithium-ion battery is 100 ppm-8000 ppm, and the N coating amount is preferably controlled within the above range, which is beneficial to further improve the electrochemical performance of the positive electrode material.

[0080] The lithium-ion battery positive electrode material provided by the embodiment of the present invention has a good high-temperature cycle life. After 1000 cycles of 1C / 1C charge and discharge at 45°C, the capacity retention rate can reach 95%, which is about 5-10% higher than the prior art. The lithium-ion battery positive electrode material prepared by the embodiment of the present invention has a reduced exothermic peak area, which improves the thermal stability of the positive electrode material.

[0081] An embodiment of the present invention further provides a positive electrode plate, comprising the lithium ion battery positive electrode material provided by the embodiment of the present invention, wherein the lithium ion battery positive electrode material exists in an active coating on the surface of the positive electrode current collector.

[0082] An embodiment of the present invention further provides a secondary battery, including the positive electrode plate provided by the embodiment of the present invention, and may also include a negative electrode plate, an electrolyte, a separator, etc., to form a complete battery structure.

[0083] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0084] Example 1

[0085] This embodiment provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:

[0086] (1) Preparation of salt solution: nickel sulfate, cobalt sulfate and manganese sulfate were dissolved in deionized water at a molar ratio of nickel to cobalt to manganese of 63:9:28 to form a mixed solution A with a total metal ion concentration of 2 mol / L.

[0087] (2) Preparation of alkaline solution: dissolve NaOH in deionized water to obtain a mixed solution B with a concentration of 4 mol / L; dissolve ammonia water in deionized water to obtain a mixed solution C with a concentration of 2 mol / L.

[0088] (3) Preparation of nickel-cobalt-manganese-aluminum hydroxide precursor: Mixed solution B, mixed solution C and water are added to a reactor to prepare a bottom solution, so that the pH value of the bottom solution is 11 and the concentration of ammonia water is 2 mol / L. Mixed solution A prepared in step (1) and mixed solution B and mixed solution C prepared in step (2) are added in parallel to the reaction vessel, and the addition rate of mixed solution A is controlled to be 50 ml / h, so that the power obtained per unit volume of solution is 1.3 kW / m 3 By adjusting the addition rate of mixed solution B and mixed solution C, the pH value of the precipitation process was 11, the concentration of ammonia in the reactor was 2 mol / L, the reaction temperature of the deposition process was controlled to be 60°C, and the power per unit volume was controlled to be 1.3 kW / m 3 The whole process of the reaction was protected by nitrogen. Zinc powder (0.4 mol) was continuously added during the reaction. The reaction was continued with stirring and growth. The reaction was stopped when the crystals grew to 4-5 μm. The obtained precipitate was filtered, washed, and dried at 120° C. for 12 h to prepare a precursor doped with metal oxide.

[0089] (4) The precursor in step (3) is mixed with lithium hydroxide in a mixer, and the molar ratio of lithium element in lithium hydroxide to the total amount of nickel, cobalt, manganese and zinc in the precursor is controlled to be 1.03:1. The mixed material is sintered in a high-temperature furnace with air atmosphere, and the high-temperature furnace is heated to 950°C at a heating rate of 5°C / min and kept at this temperature for 12 hours. After the material is naturally cooled in the furnace, it is crushed and pulverized to a particle size D50 of 3-4 μm.

[0090] (5) Mix the dried material in step (4) with the N compound (WO 3 ) are mixed evenly in a mixer, and secondary sintering is performed in an oxygen atmosphere. The temperature is raised to 600°C in a high-temperature furnace at a heating rate of 3°C / min and kept warm for 8 hours. Finally, the final doped positive electrode material is obtained by screening, and the coating amount of the N element is controlled to be 3000ppm.

[0091] Comparative Example 1

[0092] This comparative example provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:

[0093] (1) Preparation of salt solution: Same as in Example 1.

[0094] (2) Preparation of alkaline solution: same as in Example 1.

[0095] (3) Preparation of nickel-cobalt-manganese-aluminum hydroxide precursor: The only difference from Example 1 is that the metal powder is replaced by adding metal oxide (i.e., ZnO, and the molar amount of zinc is controlled to be the same as that in Example 1). The specific steps are as follows:

[0096] Mixed solution B, mixed solution C and water were added to the reactor to prepare a bottom solution, so that the pH value of the bottom solution was 11 and the ammonia concentration was 2 mol / L. Mixed solution A prepared in step (1) and mixed solution B and mixed solution C prepared in step (2) were added in parallel in the reaction vessel, and the addition rate of mixed solution A was controlled to be 50 ml / h, so that the power obtained per unit volume of solution was 1.3 kW / m 3 By adjusting the addition rate of mixed solution B and mixed solution C, the pH value of the precipitation process was 11, the concentration of ammonia in the reactor was 2 mol / L, the reaction temperature of the deposition process was controlled to be 60°C, and the power per unit volume was controlled to be 1.3 kW / m 3 The whole process of the reaction was protected by nitrogen. Metal oxide (zinc oxide, the amount of zinc was the same as in Example 1) was continuously added during the reaction. The reaction was continuously stirred and grown. The reaction was stopped when the crystals grew to 4-5 μm. The obtained precipitate was filtered, washed, and dried at 120° C. for 12 h to prepare a precursor doped with metal oxide.

[0097] (4) Same as Example 1.

[0098] (5) Same as Example 1.

[0099] (6) Same as Example 1.

[0100] Comparative Example 2

[0101] This comparative example provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:

[0102] (1) Preparation of salt solution: Same as in Example 1.

[0103] (2) Preparation of alkaline solution: same as in Example 1.

[0104] (3) Preparation of nickel-cobalt-manganese-aluminum hydroxide precursor: The only difference from Example 1 is that the metal powder is replaced by a metal salt (i.e., ZnCl 2 , controlling the molar amount of zinc is the same as in Example 1). The specific steps are as follows:

[0105] Mixed solution B, mixed solution C and water are added to the reactor to prepare a bottom solution, so that the pH value of the bottom solution is 11 and the concentration of ammonia water is 2 mol / L. Mixed solution A prepared in step (1) and mixed solution B and mixed solution C prepared in step (2) are added in parallel in the reaction vessel, and the addition rate of mixed solution A is controlled to be 50 ml / h, so that the power obtained per unit volume of solution is 0.3-6 kW / m 3 By adjusting the addition rate of mixed solution B and mixed solution C, the pH value of the precipitation process was 11, the concentration of ammonia in the reactor was 2 mol / L, the reaction temperature of the deposition process was controlled to be 60°C, and the power per unit volume was controlled to be 1.3 kW / m 3 The entire reaction process was protected by nitrogen, and metal salts (i.e. ZnSO 4 , the molar amount of zinc is controlled to be the same as in Example 1), the reaction is continued to stir and grow, and the reaction is stopped when the crystal grows to 4-5 μm. The obtained precipitate is filtered, washed, and dried at 120° C. for 12 h to prepare a precursor doped with metal oxide.

[0106] (4) Same as Example 1.

[0107] (5) Same as Example 1.

[0108] (6) Same as Example 1.

[0109] It should be noted that when preparing the precursor, due to the difference in Ksp of different salt solutions, the doping uniformity is difficult to control, resulting in an unstable internal structure of the crystal material. During the cycle, the particles produce microcracks due to uneven internal stress. The damage caused by mechanical force and internal stress provides gaps for the penetration of the electrolyte, resulting in more side reactions, thereby accelerating the decay of the battery capacity.

[0110] Comparative Example 3

[0111] This comparative example provides a method for preparing a positive electrode material for a lithium-ion battery, which differs from Example 1 only in that a doping element is added during the first sintering. The method comprises the following steps:

[0112] (1) Preparation of salt solution: Same as in Example 1.

[0113] (2) Preparation of alkaline solution: same as in Example 1.

[0114] (3) Preparation of nickel-cobalt-manganese-aluminum hydroxide precursor:

[0115] The specific steps are as follows: Mixed solution B, mixed solution C and water are added to a reactor to prepare a bottom solution, so that the pH value of the bottom solution is 11 and the ammonia concentration is 2 mol / L. Mixed solution A prepared in step (1) and mixed solution B and mixed solution C prepared in step (2) are added in parallel in a reaction vessel, and the addition rate of mixed solution A is controlled to be 50 ml / h, so that the power obtained per unit volume of solution is 0.3-6 kW / m 3 By adjusting the addition rate of mixed solution B and mixed solution C, the pH value of the precipitation process was 11, the concentration of ammonia in the reactor was 2 mol / L, the reaction temperature of the deposition process was controlled to be 60°C, and the power per unit volume was controlled to be 1.3 kW / m 3 The whole process of the reaction was protected by nitrogen, and the reaction was continuously stirred and grown. The reaction was stopped when the crystals grew to 4-5 μm. The obtained precipitate was filtered, washed, and dried at 120° C. for 12 h to prepare a precursor doped with metal oxide.

[0116] (4) The precursor in step (3) is mixed with lithium hydroxide and zinc oxide in a mixer, and the molar ratio of lithium element in lithium oxide to the total amount of nickel, cobalt, manganese and zinc in the precursor is controlled to be 1.03:1, and the molar amount of zinc in zinc oxide is the same as that in Example 1. The mixed material is sintered in a high-temperature furnace with air atmosphere, and the high-temperature furnace is heated to 950°C at a heating rate of 5°C / min and kept at this temperature for 12 hours. After the material is naturally cooled in the furnace, it is crushed and pulverized to a particle size of 3-4 μm.

[0117] (5) Same as Example 1.

[0118] (6) Same as Example 1.

[0119] In this comparative example, metal oxide is added during the first sintering to form a positive electrode material doped with metal ions. The doping uniformity is difficult to control and difficult to penetrate into the interior of the crystal, resulting in an unstable internal structure of the crystal material and poor long-term performance such as storage and circulation.

[0120] Test Example 1

[0121] The electrochemical properties of the positive electrode materials prepared in the test examples and comparative examples are shown in Table 1 and Figure 1 shown.

[0122] Test method: The positive electrode material, conductive carbon and binder (PVDF) obtained in the above embodiments and comparative examples are mixed in a ratio of 97.5:1.5:1 to prepare a slurry, and then the slurry is coated on an aluminum foil, dried, rolled, slit and die-cut, and finally assembled with a graphite negative electrode into a 5AH soft-pack battery. After preparation, conventional formation is carried out. The battery after 0.33C formation is charged and discharged at a rate of 1C at 45°C within a voltage range of 2.8-4.4V, and the capacity retention rate is recorded after 1200 cycles.

[0123] Table 1 Electrochemical performance test results of positive electrode materials prepared in Examples and Comparative Examples

[0124]

[0125] From Table 1 and Figure 1 It can be seen that the electrochemical performance of the positive electrode material prepared in the embodiment of the present invention is significantly better than that of the comparative example.

[0126] Test Example 2

[0127] The positive electrode materials prepared in the examples and comparative examples were tested by differential scanning calorimetry (DSC). Figure 2 shown.

[0128] It can be seen that the exothermic peak area of ​​Example 1 is smaller, indicating lower heat release and better thermal stability;

[0129] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium ion battery precursor, characterized in that: The invention comprises a nickel-cobalt-manganese hydroxide precursor, wherein the nickel-cobalt-manganese hydroxide precursor is doped with a metal element; The metal element is an amphoteric metal element.

2. The lithium-ion battery precursor according to claim 1, characterized in that: The metal element exists in the lithium-ion battery precursor in the form of intercalation doping; Preferably, the metal element in the metal oxide is selected from at least one of Al, Zn, Ga, Ge, In, Sn, Sb, Tl, Pb and Bi; Preferably, the metal element in the metal oxide is Zn.

3. The lithium-ion battery precursor according to claim 1 or 2, characterized in that: The chemical formula of the lithium-ion battery precursor is Ni x Co y Mn (1-x-y-z) M Z O(OH)2, M represents an amphoteric metal element, 0.8≥x≥0.5, 0.05≥y≥0, 0.05≥z≥0.

4. A method for preparing a lithium ion battery precursor according to any one of claims 1 to 3, characterized in that: include: The lithium-ion battery precursor is prepared by a coprecipitation method using nickel salt, cobalt salt and manganese salt as raw materials; During the coprecipitation process, metal powder containing the amphoteric metal element is added.

5. The preparation method according to claim 4, characterized in that: include: Providing a mixed salt solution containing the nickel salt, the cobalt salt and the manganese salt; providing a precipitant solution and a complexing agent solution; The mixed salt solution, the precipitant solution and the complexing agent solution are introduced into a reactor for coprecipitation reaction. During the reaction, the metal powder is added together with the mixed salt solution until the reaction is completed. The reaction is stopped when the crystal particle size reaches 2μm-6μm.

6. The preparation method according to claim 5, characterized in that: The molar ratio of nickel, cobalt, manganese and amphoteric metal elements added during the reaction is x:y:(1-xyz):z; 0.8≥x≥0.5, 0.05≥y≥0, 0.05≥z≥0; Preferably, the pH value of the coprecipitation reaction is controlled to be 9-13, and the concentration of the complexing agent in the reactor is 0.4-10; Preferably, the total concentration of metal elements in the mixed salt solution is 0.1mol / L-2mol / L, the concentration of the precipitant solution is 0.4mol / L-10mol / L; the concentration of the complexing agent solution is 0.4mol / L-10mol / L; More preferably, the precipitant solution is a sodium hydroxide solution, and the complexing agent solution is an ammonia solution; More preferably, the mixed salt solution addition rate is controlled to be 40 mL / h-60 mL / h, so that the power obtained per unit volume of solution is 0.3-6 kW / m 3 .

7. A positive electrode material for a lithium ion battery, characterized in that: Its chemical formula is LiNi x Co y Mn (1-x-y-z) M z O2@N a O; Wherein, M is an amphoteric metal element; N represents a surface coating element, and N is selected from at least one of B, Zr, Ti, La, V, Mo, Cr, Zn, W and Al; 0.8 ≥ x ≥ 0.5, 0.05 ≥ y ≥ 0, 0.05 ≥ z ≥ 0; Preferably, M is selected from the lithium ion battery positive electrode material in the form of intercalation doping; M is selected from at least one of Al, Zn, Ga, Ge, In, Sn, Sb, Tl, Pb and Bi; Preferably, the content of M in the lithium ion battery positive electrode material is 100 ppm-10000 ppm.

8. A method for preparing a positive electrode material for a lithium ion battery, characterized in that: A lithium-ion battery precursor is prepared by the preparation method according to any one of claims 4 to 6, and the lithium-ion battery precursor is mixed with a lithium source and sintered once; Preferably, the molar ratio of the lithium element in the lithium source to the total amount of nickel, cobalt, manganese and amphoteric metal elements in the lithium ion battery precursor is controlled to be (0.9-1.2):1:(0.1-1); preferably, sintering is performed once in an oxygen-containing atmosphere, the sintering temperature is controlled to be 600°C-1100°C, and the sintering time is 3h-20h.

9. The preparation method according to claim 8, characterized in that: After the primary sintering, the obtained material is mixed with a compound containing the N element for secondary sintering; N is selected from at least one of B, Zr, Ti, La, V, Mo, Cr, Zn, W and Al; Preferably, the secondary sintering is carried out in an oxygen-containing atmosphere, the secondary sintering temperature is controlled to be 300° C.-800° C., and the sintering time is 3 h-20 h; Preferably, the material obtained after the primary sintering is first crushed, then washed and dried, and then mixed with a compound containing the N element for secondary sintering.

10. A secondary battery, characterized in that: The invention comprises the lithium ion battery positive electrode material according to claim 7 or the lithium ion battery positive electrode material prepared by the preparation method according to any one of claims 8 to 9.